Ebola - Podlipnik, Crtomir (IntechOpen, 2016)
The book Ebola is a relevant resource of knowledge about various aspects of the Ebola virus (EBOV) and the related disease. Many experts from different fields of science and from different parts of the world contributed to the creation of this book. The book contains valuable information about firsthand experience of managing Ebola virus disease (EVD) in Third World countries and offers the best practices to handle possible pandemic outbreaks of Ebola. Detailed analysis of EBOV genome is also given, with the description of EBOV pathology supported with structural information, and in addition, the various tasks and strategies for the development of an effective anti-Ebola cure are proposed.